Anxiety Disorders in Patients With Somatic Diseases. Issue 3 (April 2020) - Henning, Michaela; Subic-Wrana, Claudia; Wiltink, Jörg; Beutel, Manfred
ABSTRACT: Objective: Anxiety disorders are among the most frequent mental disorders and are associated with a range of short- and long-term impairments and disabilities. Relatively little is known about anxiety disorders in patients with somatic diseases, and the present literature review highlights the current research in this field, data about prevalences of anxiety disorders in patients with somatic diseases, and the effectiveness of interventions. This article also introduces a comprehensive model of inpatient treatment and summarizes the evidence pertinent to this approach. Methods: A narrative review is presented with regard to prevalence and treatment of anxiety disorders in patients with somatic diseases. The effects of inpatient treatment are illustrated based on a case report. Results: This review indicates that anxiety disorders are more common in patients with somatic diseases, with prevalence estimates ranging from 2.5% to 55%, than in the general population. Several outpatient treatment options exist, with substantial support for the effectiveness of cognitive behavioral therapy, psychodynamic therapy, and pharmacotherapy. We also provide evidence in support of psychosomatic inpatient treatment for patients with anxiety disorders that are comorbid with somatic diseases. Conclusions: Anxiety disorders are common in patients with somatic diseases, and several effective treatment options exist, including cognitive behavioral therapy and pharmacological interventions. We also provide support for the effectiveness of inpatient treatment with unique opportunities for multidisciplinary psychosomatic treatment of anxiety disorders with comorbid somatic diseases. Abstract : Supplemental digital content is available in the text.